MicroRNA-155 Regulates MAIT1 and MAIT17 Cell Differentiation - Liu, Tingting; Wang, Jie; Subedi, Kalpana; Yi, Qijun; Zhou, Li; Mi, Qing-Sheng (Frontiers in Cell and Developmental Biology, 2021)
Mucosal-associated invariant T (MAIT) cells are innate-like T cells that develop in the thymus through three maturation stages to acquire effector function and differentiate into MAIT1 (T-bet+) and MAIT17 (RORγt+) subsets. Upon activation, MAIT cells release IFN- and IL-17, which modulate a broad spectrum of diseases. Recent studies indicate defective MAIT cell development in microRNA deficient mice, however few individual miRNAs have been identified to regulate MAIT cells. MicroRNA-155 (miR-155) is a key regulator of numerous cellular processes that affect some immune cell development, but its role in MAIT cell development remains unclear. To address whether miR-155 is required for MAIT cell development, we performed gain-of-function and loss-of-function studies. We first generated a CD4Cre.miR-155 knock-in mouse model, in which miR-155 is over-expressed in the T cell lineage. We found that overexpression of miR-155 significantly reduced numbers and frequencies of MAIT cells in all immune organs and lung, blocked thymic MAIT cell maturation through downregulating PLZF expression, and increased CD8+ subset and decreased CD4-CD8- subset of MAIT cells. Strikingly, upregulated miR-155 promoted MAIT1 differentiation and blocked MAIT17 differentiation, and timely inducible expression of miR-155 functionally inhibited peripheral MAIT cells secreting IL-17. We further analyzed MAIT cells in conventional miR-155 knockout mice and found that lack of miR-155 also promoted MAIT1 differentiation and blocked MAIT17 differentiation but without alteration of their overall frequency, maturation and function. Overall, our results indicate that adequate miR-155 expression is required for normal MAIT1 and MAIT17 cell development and function.